Politik Nahdatul Ulama dan Orde Baru - Nurlira Goncing (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : Nahdlatul Ulama (NU) is a faith-based and community organizations whose existence plays an important role for the life of the nation. As one of the largest organization in the country, it is definitely social responsibility carried NU also great and take a position in the political sphere. This attitude is not only taken to protect the leaders and citizens of the process of degradation and demoralization of politics, but also to maintain the integrity of the state in the new order era.Keywords: Nahdatul Ulama Politics, New Order Era, Indonesia